c,
I-1/3I+(-1/2)^2:I-2I-2021^0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Chọn B.
Ta có: (2 - 3i).(1 + 2i) = 2 + 4i - 3i - 6i2 = 8 + i
Từ giả thiết : (1 + i)z + (2 - 3i)(1 + 2i) = 7 + 3i nên
(1 + i)z + (8 + i) = 7 + 3i hay (1 + i)z = -1 + 2i
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 + 2i)[(2 – i) + (3 – 2i)]
= (3 + 2i)(5 – 3i) = 21 + i
b)(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i
c) (1 + i)2 – (1 - i)2 = 2i – (-2i) = 4i
d) 3+i2+i−4−3i2−i=(3+i)(2−i)5−(4−3i)(2+i)5=7−i5−11−2i5=−45+15i
![](https://rs.olm.vn/images/avt/0.png?1311)
a) |x + 2| - x = 2
=> |x + 2| = x + 2
=> x + 2 >= 0
=> x >= -2
b) |x - 3| + x - 3 = 0
=> |x - 3| = 3 - x
=> x - 3 <= 0
=> x <= 3
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (3 + 4i)x = (1 + 2i)(4 + i)
b) 2ix + 3 = 5x + 4i
c) 3x(2 – i) + 1 =2ix(1 + i) + 3i
\(=\dfrac{1}{3}+\dfrac{1}{4}:2-1=\dfrac{1}{3}+\dfrac{1}{2}-1=\dfrac{5}{6}-1=-\dfrac{1}{6}\)